A problem on my (last week's) real analysis homework boiled down to proving that, for $a>-1$, $$\sum_{n=1}^\infty\frac{(n-1)!}{n\prod\limits_{i=1}^n(a+i)}=\sum_{k=1}^\infty \frac{1}{(a+k)^2}.$$ Mathematica confirms this is true, but I couldn't even prove the convergence of the original series (the one on the left), much less demonstrate that it equaled this other sum; the ratio test is inconclusive, and the root test and others seem hopeless. It was (and is) quite a frustrating problem. Can someone explain how to go about tackling this?

  • 2
    $\begingroup$ You can obtain convergence using Raabe's Ratio Test. $\endgroup$ – xen Oct 25 '11 at 8:51
  • $\begingroup$ Would going the hypergeometric route be a nuke for you here? $\endgroup$ – J. M. isn't a mathematician Oct 25 '11 at 9:05
  • $\begingroup$ @J.M. I'm only vaguely familiar with hypergeometric series, but certainly I'd be interested in whatever approach you have; however, this occurred in a problem in Chapter 2 of Folland's Real Analysis, and I don't believe that we are assumed to have seen hypergeometric series before, so I would hope there is some relatively straightforward way of proving it. $\endgroup$ – Zev Chonoles Oct 25 '11 at 9:11
  • 1
    $\begingroup$ @Hans: methinks the difference calculus route could be pedagogical; I say go for it! $\endgroup$ – J. M. isn't a mathematician Oct 25 '11 at 10:21
  • 4
    $\begingroup$ This was rather a fun question to watch evolving; thanks to everyone! The only thing missing now is a combinatorial proof using objects counted by generating functions given by the summands on the two sides :-) $\endgroup$ – joriki Oct 25 '11 at 10:46

This uses a reliable trick with the Beta function. I say reliable because you can use the beta function and switching of the integral and sum to solve many series very quickly.

First notice that $$\prod_{i=1}^{n}(a+i)=\frac{\Gamma(n+a+1)}{\Gamma(a+1)}.$$ Then

$$\frac{(n-1)!}{\prod_{i=1}^{n}(a+i)}=\frac{\Gamma(n)\Gamma(a+1)}{\Gamma(n+a+1)}=\text{B}(n,a+1)=\int_{0}^{1}(1-x)^{n-1}x{}^{a}dx.$$ Hence, upon switching the order we have that $$\sum_{n=1}^{\infty}\frac{(n-1)!}{n\prod_{i=1}^{n}(a+i)}=\int_{0}^{1}x^{a}\left(\sum_{n=1}^{\infty}\frac{(1-x)^{n-1}}{n}\right)dx.$$ Recognizing the power series, this is $$\int_{0}^{1}x^{a}\frac{-\log x}{1-x}dx.$$ Now, expand the power series for $\frac{1}{1-x}$ to get $$\sum_{m=0}^{\infty}-\int_{0}^{1}x^{a+m}\log xdx.$$ It is not difficult to see that $$-\int_{0}^{1}x^{a+m}\log xdx=\frac{1}{(a+m+1)^{2}},$$ so we conclude that $$\sum_{n=1}^{\infty}\frac{(n-1)!}{n\prod_{i=1}^{n}(a+i)}=\sum_{m=1}^{\infty}\frac{1}{(a+m)^{2}}.$$

Hope that helps,

Remark: To evaluate the earlier integral, notice that $$-\int_{0}^{1}x^{r}\log xdx=\int_{1}^{\infty}x^{-(r+2)}\log xdx=\int_{0}^{\infty}e^{-u(r+1)}udu=\frac{1}{(r+1)^{2}}\int_{0}^{\infty}e^{-u}udu. $$ Alternatively, as Joriki pointed out, you can just use integration by parts.

| cite | improve this answer | |
  • $\begingroup$ +1, very nice. You can also get that last integral by integration by parts. $\endgroup$ – joriki Oct 25 '11 at 9:26
  • $\begingroup$ @Joriki: Hmmm that is a good point! Certainly the easier way. (I was in the Gamma Function mindset) $\endgroup$ – Eric Naslund Oct 25 '11 at 9:27
  • 5
    $\begingroup$ I see my trouble now; the original problem was actually to show that $$\int_0^1x^a(1-x)^{-1}\log(x)\,dx=\sum_{k=1}^\infty\frac{1}{(k+a)^2}$$ with the instruction to expand as an infinite series and justify switching the order; but I expanded the logarithm, and ended up at the series $$\sum_{n=1}^{\infty}\frac{(n-1)!}{n\prod_{i=1}^{n}(a+i)}$$ with nowhere to go :) Thanks for your excellent answer! $\endgroup$ – Zev Chonoles Oct 25 '11 at 9:36
  • 2
    $\begingroup$ @Eric: Induction on $n$; for $n=0$ we know it's $\frac{1}{a+1}$, then using integration by parts I got $$\int_0^1x^a(x-1)^{k}\,dx=\left.\frac{x^{a+1}(x-1)^{k}}{a+1}\right|_0^1-\frac{k}{a+1}\int_0^1x^{a+1}(x-1)^{k-1}\,dx=$$ $$(0-0)-\frac{k}{a+1}\left(\int_0^1x^{a+1}(x-1)^{k-1}\,dx\right)$$ which shows that $$\int_0^1x^a(x-1)^{n}\,dx=\frac{(-1)^{n}n!}{\prod_{i=1}^{n+1}(a+i)}$$ $\endgroup$ – Zev Chonoles Oct 25 '11 at 9:43
  • 1
    $\begingroup$ @Zev: oooo right, because $k$ is still an integer! Ok thanks, that is very good! You might also like the proof on Wikipedia for the Beta function/ Gamma function identity. It is basically all the one needs to know about the beta function: (cool integration tricks in the plane) en.wikipedia.org/wiki/… $\endgroup$ – Eric Naslund Oct 25 '11 at 9:47

Since at least J. M. asked for it, here's another solution for the case when $a$ is a natural number.

I'll use the forward difference operator $\Delta$, defined by $\Delta f(n) = f(n+1) - f(n)$, and the falling factorial defined by $$ n^{\underline{a}} = \begin{cases} n(n-1)(n-2) \dots (n-a+1), & a > 0, \\ 1, & a=0 \\ \frac{1}{(n+1)(n+2) \dots (n+|a|)}, & a < 0, \end{cases} $$ and satisfying $\Delta n^{\underline{a}} = a n^{\underline{a-1}}$.

The summand, which I'll denote by $F_a(n)$, can be rewritten as $$ F_a(n) = \frac{(n-1)!}{n\prod_{i=1}^n(a+i)} = \frac{(n-1)! a!}{n (a+n)!} = \frac{a!}{n \cdot n(n+1)(n+2) \dots (n+a)} $$ $$= \frac{(a-1)!}{n} \left( -(-a) (n-1)^{\underline{-(a+1)}}\right) = -\frac{(a-1)!}{n} \Delta\left( (n-1)^{\underline{-a}}\right). $$ Using the rule $\Delta(f(n)g(n)) = \Delta f(n) \, g(n+1) + f(n) \Delta g(n)$, we get $$ F_a(n) = - \Delta\left( \frac{(a-1)!}{n} (n-1)^{\underline{-a}}\right) + \Delta\left( \frac{(a-1)!}{n} \right) \, n^{\underline{-a}} $$ $$ = - \Delta\left( \frac{(a-1)!}{n \cdot n (n+1) \dots (n+a-1)} \right) + (a-1)! \left( \frac{1}{n+1} - \frac{1}{n} \right) \frac{1}{(n+1)\dots (n+a)} $$ $$= - \Delta\left( \frac{(a-1)!}{n \cdot n(n+1) \dots (n+a-1)} \right) + F_{a-1}(n+1) - (a-1)! \Delta\left( \frac{(n-1)^{\underline{-a}}}{-a} \right). $$

Summing over $n \ge 1$ gives (because of telescoping in the sums-of-deltas) $$ \sum_{n=1}^{\infty} F_a(n) = \frac{(a-1)!}{1 \cdot a!} + \sum_{n=1}^{\infty} F_{a-1}(n+1) - \frac{(a-1)!}{a} 0^{-\underline{a}} $$ $$ = \frac{1}{a} + \sum_{m=2}^{\infty} F_{a-1}(m) - \frac{1}{a^2} $$ $$ = \sum_{m=1}^{\infty} F_{a-1}(m) - \frac{1}{a^2} $$ (since $F_{a-1}(1) = 1/a$).

Finally, since $F_0(n) = 1/n^2$, we obtain after using this result to work our way down $n$ steps that $$ \sum_{n=1}^{\infty} F_a(n) = \sum_{n=1}^{\infty} F_{a-1}(n) - \frac{1}{a^2} = \dots = \sum_{n=1}^{\infty} F_0(n) - \left( \frac{1}{a^2} + \dots + \frac{1}{1^2} \right) = \sum_{n=a+1}^{\infty} \frac{1}{n^2} = \sum_{k=1}^{\infty} \frac{1}{(k+a)^2}. $$

| cite | improve this answer | |
  • $\begingroup$ I was expecting you'd be using a as the base and then connect rising and falling factorials, but this is nice! $\endgroup$ – J. M. isn't a mathematician Oct 26 '11 at 3:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.